PROFIL KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MTS NEGERI 1 TOLITOLI DALAM MENYELESAIKAN SOAL CERITA SEGITGA SIKU-SIKU BERDASARKAN GAYA BELAJAR: Profile Of Mathematic Communication Ability Of Students Of MTs Negeri 1 Tolitoli In Solving Story Questions Based On Learning Style - Mansur, Meliani; Hadjar, Ibnu; Murdiana, I Nyoman; Lefrida, Rita (Jurnal Elektronik Pendidikan Matematika Tadulako, 2024)
This study aims to obtain a description of the mathematical communication skills of class IX Dzulhijjah 2 MTs Negeri 1 Tolitoli students in solving right triangle story problems. This type of research is descriptive with a qualitative approach. The subjects of this study were students of class IX Dzulhijjah 2 MTs Negeri 1 Tolitoli whose learning styles were visual, auditory, and kinesthetic. Data were collected through written assignments and interviews. The results of this study indicate that (1) The profile of mathematical communication skills of visual learning style subjects is able to write down information that is known and asked completely, and also the subject is able to describe a right triangle that corresponds to the problem along with the information on the right triangle, then the subject is able to using steps in solving problems, and the subject is able to conclude the answers obtained at the end of completion. (2) The profile of mathematical communication skills of auditory learning style subjects is able to write down information that is known and asked completely, and also the subject is able to describe a right triangle that corresponds to the problem along with the information on the right triangle, then the subject is able to use the steps in solve problems (3) The profile of mathematical communication skills, subjects with kinesthetic learning style are able to write down information that is known and asked completely, and also the subject is able to describe a right triangle in accordance with the problem along with the information on the right triangle, then the subject is able to use the following steps: steps in solving the problem.